2019
DOI: 10.4149/gpb_2018035
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin reduced endometrial hyperplasia induced by estradiol in female albino rats

Abstract: Melatonin, the pineal gland hormone, plays a crucial role in regulation of neuroendocrine and defensive functions, free radicals neutralization, and suppresses angiogenesis, proliferation and cancer. The purpose of designing our study is to assess the effect of estradiol benzoate and its combination with melatonin on uteri of female albino rats. For 4 weeks, the present study was conducted on thirty six female rats separated into 3 groups: Control group (rats received the vehicle), EB group (rats were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Consistent with the current study, previous reports [ 29 , 49 ] demonstrated similar findings in connection with the ability of EB to decrease cleaved caspase 3, an apoptosis marker, in EB-induced EH in rats. On the other hand, the EH+IRB-treated rats showed higher uterine cleaved caspase 3 compared to EH untreated rats.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the current study, previous reports [ 29 , 49 ] demonstrated similar findings in connection with the ability of EB to decrease cleaved caspase 3, an apoptosis marker, in EB-induced EH in rats. On the other hand, the EH+IRB-treated rats showed higher uterine cleaved caspase 3 compared to EH untreated rats.…”
Section: Discussionsupporting
confidence: 93%
“…However, this relationship was not observed in the healthy and pregnant groups. On the other hand, it was also stated that there may be a relationship between endometrial hyperplasia and oxidative stress in women (Gomez‐Zubeldia et al., 2008; Pejic et al, 2015) and rats (Abdel‐Hamid et al., 2019). However, according to our best literature knowledge, no study has been conducted investigating the relationship between oxidative stress and asymptomatic CEH in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs including toremifene, genistin, daidzin, glycyrrhizae radix, glycyrrhizin, Juzen-taiho-to and Shimotsu-to inhibited the estrogen-related EC carcinogenesis by downregulating IL-1α ( 32 36 ). And the adverse histopathological changes in endometrium induced by estradiol benzoate can be reduced or prevented by diacerein via downregulating IL-1β ( 97 ), irbesartan via upregulating IL-10 ( 98 ) and melatonin via upregulating IL-2 ( 99 ).…”
Section: Roles Of Interleukins In Ecmentioning
confidence: 99%